Genotyping of Virulence Factors of Uropathogenic Escherichia Coli from Chittagong, Bangladesh (Chittagong University Journal of Biological Sciences, 2024)
UropathogenicEscherichia coli are the common cause of Urinary Tract Infection affecting 150 million people each year worldwide. In this study,we investigated the prevalence of UPEC genetic regions coding for various virulence factors.The targeted genetic determinants were those coding for pili associated with pyelonephritis (pap),hemolysin (hly),cytotoxic necrotizing factor (cnf) and aerobactin (aer). We collected 180 urine samples ofUTI patients from the Chittagong region of Bangladesh and isolated UPEC.Among the studied strains the prevalence of pap,hly, cnfand aer genes were 21,25.2,24.3 and 7.0%respectively.This rapid assessment of the bacterial pathogenicity may contribute to a better medical approach for the patients with urinary tract infections.The Chittagong Univ. J. B. Sci. 9(1&2):39-48,2019